Design and analysis of a graded honeycomb shock absorber for a helicopter seat during a crash condition. Issue 3 (3rd May 2016) - Galehdari, S.A.; Khodarahmi, H.
ABSTRACT: An important issue that should be considered in accidents, including car, helicopter, and airplane crashes, is the safety of the human occupants. In this research, graded honeycomb structure is primarily introduced as a shock absorber. The amount of energy absorption, and the applied force and acceleration to the passengers have been calculated through numerical simulation in ABAQUS software. In order to validate numerical results, a low velocity experiment has been conducted on the test sample. Results represent an acceptable agreement with empirical ones. Given the occurrence of an emergency helicopter crash, it is of great importance to avoid any potential injurious loading to the passenger. Hence, according to Joint Aviation Regulations part 27, an optimised seat shock absorber has been designed and analysed for a helicopter in crash condition by the means of Genetic and Sequential Quadratic Programming algorithms. The designed shock absorber, which is of graded honeycomb structure, has satisfied complete standard specifications while being applied in the helicopter crash simulation. The applied design and simulation approach could be extended for any other types of shock absorbers.